PROGRAM LANSIA AKTIF MANDIRI (LAMAR) DALAM UPAYA DETEKSI DINI OSTEOARTHRITIS - Maria Orizani, Chindy; Putri, Linta Meyla; Wijaya, Hermanto (PPM STIKES Adi Husada, 2023)
Introduction & Aim: Physical changes in the elderly include the musculoskeletal system, where there is a decrease in the production of synovial fluid as a joint lubricant causing impaired joint movement. Joint disorders are characterized by symptoms of joint stiffness or pain when moving. So far, activities at the elderly integrated service post (posyandu) include promotive and preventive activities. Still, the material presented has not shown any screening or early detection of joint stiffness due to osteoarthritis, even though many elderly people complain of joint stiffness and pain. Therefore, the purpose of this community service activity is to make the elderly remain active independently (LAMAR) to detect early symptoms of osteoarthritis using a goniometer. Method of Activity: This community service activity was carried out in February 2023 in the RW 7 area, Kapasan Village, Simokerto District, Surabaya City. The activity begins with an initial assessment of the elderly who are members of the elderly posyandu in the area. The activities carried out included the initial socialization of the LAMAR program, implementation of counseling, conducting early detection demonstrations, and program evaluation. The results of the screening were then processed using computer software. Results: The knowledge of the elderly after being given counseling on the Independent Active Elderly program through the media of booklets, power points, and goniometer teaching aids has been shown to increase where the statistical test results were p = 0.002 (α≤0.05) from 48% of respondents with sufficient and insufficient knowledge to 100% with a good level of knowledge. Discussion: The LAMAR (Independent Active Elderly) program will make the elderly productive, namely the elderly who are physically, mentally, and socially healthy. This can increase awareness/attention to the elderly in early detection of joint stiffness. The goniometer is used to measure and record the amount of joint movement actively or passively.